Teaching (remotely) to communicate (remotely) with relatives of patients during lockdown due to the COVID-19 pandemic - Ara Ayora; Carme Nogueras; Sonia Jiménez-Panés; Sergi Cortiñas-Rovira (PEC Innovation, 2023)
Aim: In 2020, due to the pandemic, the lack of specific knowledge on breaking bad news over the phone became apparent. This study aims at assessing the differences, or lack thereof, in satisfaction reported by participants in the different formats of a course in telephone communication for breaking bad news to families of patients, developed based on the previous experience of a team dedicated to this task during the peak of the pandemic. Methods: Four courses were delivered, two in a fully streamed format and two in a blended format, part pre-recorded, part streamed. There were 41 attendants, mostly doctors, but also nurses, social workers, occupational therapists, and administrative staff who deal with families. Subsequently, a survey was conducted to assess the degree of satisfaction of the participants. Results: Both formats scored very positively, with small advantages for the fully streamed format, mainly due to the difference in interaction activities. Conclusions: The main conclusion is the need for these courses, which are demanded by the professionals themselves, without forgetting the benefit obtained from interprofessional education that enriches interaction and learning. Innovation: The inclusion of administrative staff allows for a global vision of care for family members, which improves it.